Animal Board Invited Review: Sheep birth distribution in past herds: a review for prehistoric Europe (6th to 3rd millennia BC). (23rd May 2017) - Balasse, M.; Tresset, A.; Bălăşescu, A.; Blaise, E.; Tornero, C.; Gandois, H.; Fiorillo, D.; Nyerges, É. Á.; Frémondeau, D.; Banffy, E.; Ivanova, M.
Abstract : In temperate latitudes sheep have a seasonal reproductive behaviour, which imposes strong constraints on husbandry in terms of work organization and availability of animal products. During the last 50 years, researchers have focused on understanding the mechanisms driving small ruminants' reproduction cycles and finding ways to control them. This characteristic is inherited from their wild ancestor. However, the history of its evolution over the 10 millennia that separates present day European sheep from their Near Eastern ancestors' remains to be written. This perspective echoes archaeologists' current attempts at reconstructing ancient pastoral societies' socio-economical organization. Information related to birth seasonality may be retrieved directly from archaeological sheep teeth. The methodology consists of reconstructing the seasonal cycle record in sheep molars, through sequential analysis of the stable oxygen isotope composition ( δ 18 O) of enamel. Because the timing of tooth development is fixed within a species, inter-individual variability in this parameter reflects birth seasonality. A review of the data obtained from 10 European archaeological sites dated from the 6th to the 3rd millennia BC is provided. The results demonstrate a restricted breeding season for sheep: births occurred over a period of 3 to 4 months, from late winter to early summer at latitudes 43°N to 48°N, while a later onset was observed at a higher latitude (59°N). All conclusions concurred with currently held expectations based on present day sheep physiology, which, aside from the historical significance, contributes to the reinforcing of the methodological basis of the approach. Further study in this area will permit regional variability attributable to technical choices, within global schemes, to be fully reported.